Anti-IgLON5 disease with distinctive brain MRI findings responding to immunotherapy: A case report. Issue 4 (29th January 2021) - Pi, Yan; Zhang, Li-li; Li, Jing-cheng
Abstract: Rationale: Anti-IgLON5 disease was first described as a progressive antibody-associated encephalopathy, with multiple non-specific clinical symptoms including sleep dysfunction, bulbar symptoms, progressive supranuclear palsy-like syndrome, cognitive impairment, and a variety of movement disorders. This newly discovered disease presents with unremarkable or unspecific brain magnetic resonance imagings (MRI), and have poor responsiveness to immunotherapy. Patient concerns: In this case, a 37-year-old man presented with 4-day history of gait instability, dysarthria, and oculomotor abnormalities. The initial neurologic examination revealed mild unsteady gait, subtle dysarthria, and left abducent paralysis. Diagnosis: The patient was diagnosed with anti-IgLON5 disease, based on clinical features and positive anti-IgLON5 antibodies in serum. Interventions: Initially, the patient was treated with high dosages of methylprednisolone and immunoglobulins. Outcomes: The symptoms of patient rapidly improved after high-dose intravenous methylprednisolone and immunoglobulins. Conclusions: In this paper, we report a new case of anti-IgLON5 disease with major symptoms of gait instability, dysarthria, and oculomotor abnormalities, with distinctive brain MRI findings, and responsive to immunotherapy.